Iconographic Analysis of the Facade of the Temple of San Francisco de Asís in Tepeapulco Hidalgo - Moreno Vidal, Carmen Fabiola (Eikón / Imago, 2017)
The facade of the temple of Tepeapulco, despite its small dimensions and its apparent simplicity, has a large number of decorative elements made for teaching purposes. This facade conceived by the friars but executed by the natives contains different symbolic messages interpreted according to the worldview of evangelizers as evangelized. The facade of San Francisco de Asís is an example of the sophisticated mixture and superposition of Christian religious meanings on prehispanic symbols, common practice during the process of evangelization in the sixteenth century in Mexico. In this article we have tried to make an analysis of the symbolism of the main components in the facade, as well as the meaning for the different cultures, of the elements with formal, conceptual and structural affinities in which the rehabilitation of pre-Hispanic symbols was given, deliberately integrated by the evangelizers within a Christian framework.